Age differences in risk taking: now you see them, now you don't. Issue 4 (4th July 2022) - Wilson, Jenna M.; Sevi, Barış; Strough, JoNell; Shook, Natalie J.
ABSTRACT: Older age has often, but not always, been associated with less risk taking. Inconsistencies may be due to diversity in the risk-taking measures used and/or individual differences in cognitive abilities. We investigated the robustness of age differences in risk taking across three measures, and tested whether age differences in risk taking remained after accounting for cognitive abilities. Younger (aged 25–36) and older (aged 60+) adults completed behavioral (i.e., Balloon Analogue Risk Task, BART) and self-report (i.e., framing tasks and Choice Dilemmas Questionnaire) measures of risk, as well as several measures of cognitive ability (i.e., analytic thinking, numeracy, processing speed, memory, and attention). Older adults showed significantly less risk taking than younger adults on the behavioral measure of risk, but not on the two self-report measures. Older adults also had significantly lower analytic thinking, slower processing speed, and worse executive control compared to younger adults. Less risk taking on the BART was associated with lower analytic thinking and numeracy, slower processing speed, and worse shifting of attention. Age differences in risk taking on the BART remained after accounting for older adults' lower scores on tests of cognitive abilities. Implications for measuring age differences in risk taking are discussed.